2018
DOI: 10.1111/liv.13941
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index as a predictor of NAFLD: A prospective study with 4‐year follow‐up

Abstract: Our findings suggest that the VAI level is an independent risk factor of NAFLD and there is a dose-response relationship between VAI level and NAFLD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Proinflammatory cytokines and chemokines produced by infiltrated macrophages could exacerbate IR and recruit more immune cells to the inflamed adipocytes [61]. It was reported in NAFLD patients that liver necroinflammation and fibrosis increased significantly with visceral fat in a dose-dependent manner [62]. Meanwhile, the adipose tissue from NAFLD patients were found with an increased expression of genes that regulate inflammation, and the adipose tissue macrophages produced increased levels of inflammatory cytokines, compared with control [63].…”
Section: Adipose Tissue and Nafldmentioning
confidence: 99%
“…Proinflammatory cytokines and chemokines produced by infiltrated macrophages could exacerbate IR and recruit more immune cells to the inflamed adipocytes [61]. It was reported in NAFLD patients that liver necroinflammation and fibrosis increased significantly with visceral fat in a dose-dependent manner [62]. Meanwhile, the adipose tissue from NAFLD patients were found with an increased expression of genes that regulate inflammation, and the adipose tissue macrophages produced increased levels of inflammatory cytokines, compared with control [63].…”
Section: Adipose Tissue and Nafldmentioning
confidence: 99%
“…This cohort was built using data from the Health Management Cohort (BHMC). The BHMC is a large-scale longitudinal cohort study that investigates the development of metabolic disorders in healthy individuals from urban areas of Beijing [8,9]. There were 11,585 participants who were recruited to undergo a physical examination in 2012.…”
Section: Study Populationmentioning
confidence: 99%
“…There were substantial researches exploring the associations of VAI with chronic diseases in human, which proved that VAI was negatively associated with insulin sensitivity [16,17] and identified as a powerful indicator for pre-diabetes or diabetes [18][19][20], and positively associated with the risk of hyperuricemia [21] and nonalcoholic fatty liver disease (NAFLD) [22]. Additionally, the results of several epidemiological studies [9,15,23] exploring the association between visceral adiposity and risk of hypertension showed that VAI was positively associated with the risk of hypertension in Chinese adult population [9] or Japanese Americans [24], and baseline scores of VAI could predict hypertension and CVD incident in prehypertension or healthy population [15,23], whereas others reported no association [25] or an association in women but not men [26].…”
Section: Introductionmentioning
confidence: 99%